The Implementation of the Prophet Muhammad's Teaching Methods in Tarbawi Hadiths: A Study of Islamic Educational Values and Their Relevance to Modern Learning - Budiyanto, Budiyanto (Journal Corner of Education, Linguistics, and Literature, 2025)
The teaching methods of Prophet Muhammad SAW, as reflected in tarbawi hadiths, offer universal Islamic educational values that remain relevant across various contexts, including modern learning. This study aims to examine the implementation of the Prophet's teaching methods, highlighting Islamic educational values and their relevance to contemporary education. A qualitative approach with a descriptive-analytic method was employed. Primary data consisted of hadiths from standard collections such as Sahih al-Bukhari and Sahih Muslim, while secondary data included tafsir (Qur'anic exegesis) and sharh (commentary on hadith). Data collection was conducted through literature study, and thematic content analysis was utilised for analysis. The findings identified four main teaching methods of the Prophet: questioning, role modelling, storytelling, and hands-on practice. The questioning method fosters critical and analytical thinking, while role modelling is pertinent to character education. Storytelling facilitates understanding of concepts through narrative techniques, and hands-on practice aligns with experiential learning approaches. The study concludes that the Prophet’s teaching methods are highly relevant to modern learning, including problem-based learning, role modelling, and project-based learning. The study recommends integrating the Prophet’s methods into Islamic education curricula and developing educational technology grounded in Islamic values to support digital learning. Practical implications include educator training and technological innovation to enhance the quality of education in Islamic institutions. Future research is recommended to empirically test the application of these methods to measure their impact on learning quality and character development.